Sanitation and gendered psychosocial stress in peri-urban Bangalore. Issue 4 (19th May 2021) - Biswas, Durba; Joshi, Shweta
ABSTRACT: Poor sanitation infrastructure can impact the physical and psychological well-being of marginalised communities. This article explores sanitation-related psychosocial stress among men and women in a peri-urban slum in Bangalore, India. It finds that women in Jayanagar slum, Karnataka, experienced psychosocial stress from open defecation due to the risk of sexual violence and socio-cultural norms. Their families also experienced stress as sexual assault on a woman can impact her family's social standing in the community. Women use multiple coping strategies, even at the cost of their overall health and hygiene. For men, anxieties emerged from the risks to the women in their families.